Evolução, perfil e sensibilidade do mercado de trabalho em segurança privada no NE no período de 2007 a 2012 - Santos, Alan Vasconcelos (2016)
This research proposes to evaluate the evolution, profile, correlation and sensitivity of private security in the labor market in relation to the perception of violence experienced by economic agents in the Northeast. This market has grown eloquently in recent years, gaining economic importance not only in major urban centers, but also in cities of smaller sizes. It is believed that such performance is associated with increased crime and sense of insecurity perceived by citizens, despite increasing investments in public safety conducted by state governments. The study takes as reference the period 2007-2012, and search initially investigate the performance of this economic sector to look into the socio-economic profile of the people who participated in this activity. To achieve this goal, it is the use of descriptive statistics tools, which allow unravel the details of this market in the northeastern region. The verification of the correlation between the level of employment in this sector and criminalities indicators, particularly homicides and the homicide rate also constitutes one of the work purposes, in which it was possible to detect a strong linear relationship between the behavior of this market with indicators of violence. In particular, for the Northeastern states found an intense association between formal employment and homicides, and a smaller magnitude correlation, although still significant for most states, when it assessed the crime by the variable homicide rate. In addition, through the application of models (non-linear) regression for count data, it was possible to estimate the job-killing elasticities for the regions of the country, with particular attention to the Northeast. The criteria and tests used, it was the superiority of the Binomial model negative front of Poisson, and of the estimates (elasticities) it became clear that the private security market has a relationship with the murders, becoming stronger by restricting analysis for the municipalities of metropolitan areas and have state penitentiaries. The point elasticities estimated in these two situations showed higher values in other cases.